PERBANDINGAN KELAYAKAN FINANSIAL USAHATANI KELAPA SAWIT PLASMA DAN SWADAYA DI KECAMATAN PELEPAT ILIR KABUPATEN BUNGO - Aprilia, Dina Rina; Sunaryanto, Lasmono Tri (Agros Journal of Agriculture Science, 2024)
Oil palm farming in Pelepat Ilir District, Bungo Regency has two farming patterns, namely plasma and independent oil palm. Differences in farming patterns affect the income and expenses earned by farmers. This study aims to determine: (1) comparison of plasma and self-help farming income, (2) comparison of the feasibility level of plasma and self-help oil palm farming. The sampling technique used purposive sampling with 30 respondents. The data used were primary data (questionnaires, interviews, observations, and documentation) and secondary data (related agencies). The analysis techniques used are R/C Ratio, Price BEP, Production BEP, and T Test. The results showed that plasma oil palm farming income was IDR 6.466.945 while self-help was higher with a value of IDR 7.871.897. The results of the T test of plasma and self-help income show Sig 0.013 or there is a difference. The R/C ratio value of plasma oil palm is 1.31 and self- help is greater with a value of 1.37, both are feasible because > 1. The BEP price of plasma oil palm business amounted to IDR 1.538/kg/ha < IDR 2.023/kg/ha and self-help of IDR 1.48/kg/ha < IDR2.031/kg/ha, which means both are feasible to run. The BEP value of plasma oil palm farming production is 10.158 kg/ha < 13.356 kg/ha and independent of 10.507 kg/ha < 14.383 kg/ha, so both are feasible because the production value is greater than the BEP value.